"There and back again" − How decapod megalopae find the way home: A modelling exercise for Pachygrapsus marmoratus. (May 2020) - Pires, Rita F.T.; Peliz, Álvaro; Pan, Maria; dos Santos, Antonina
Highlights: Physical-ecological models based on observations were developed for crab larvae. Surface exportation impacts early alongshore transport and position of late stages. Subsurface distribution of late stages increases onshore return. Distinct periods of larval emission resulted in contrasting dispersal patterns. Mid/outer shelf study complementing the existing knowledge for coastal regions. Abstract: Pachygrapsus marmoratus is a common coastal crab occurring in rocky shores of the northeastern Atlantic. The species presents a planktonic larval phase, constituting an interesting subject for dispersal studies, given the larval release in intertidal areas, followed by the exportation to shelf waters where larval development takes place. Onshore migration to the adult habitats is thought to be performed by the megalopa stage. Observations obtained during a summer zooplankton survey showed P. marmoratus larvae gradually farther from the coast throughout larval development, with early larval stages found in surface layers and megalopae occurring closer to the coast. The vertical migration mechanisms for larval dispersal and the return to settlement habitats were tested through physical-ecological models where the vertical distributions changed through the larval development. Ecological data, such as the ontogenetic vertical distribution of each larval stage, larval duration, and time and sites of spawning, were integrated in an oceanic model. Simulations tested different vertical distributions and periods, covering the entire larval development from intertidal areas to shelf and back to shore. The distribution of the early stages in surface layers promoted cross- and alongshore transport. Differences in the initial advection determined the positions where the more advanced stages were found later in the development. The subsurface distribution of advanced stages facilitated the transport to the inner shelf, limiting the cross-shore upwelling transport and promoting higher return to the adult habitats. Different periods of larval release resulted in contrasting dispersal patterns that could influence larval survival and recruitment to adult populations.